On the role of social choice, the challenges of implementing the Treaty on the establishment of a United Russian-Belarusian State of December 8, 1999 and the integration constitutionalism - S. N. Baburin (Правоприменение, 2021)
The article reproduces the speech of Sergey N. Baburin at the plenary session of the inter-national scientific conference "Law Enforcement in Public and Private Law", which was held on March 26, 2021 at the Faculty of Law of the Dostoevsky Omsk State University. The conference was dedicated to the 200th anniversary of the birth of Fedor M. Dostoevsky. On the example of the law enforcement of the norms of the Treaty on the Creation of the Union Russian-Belarusian State of 1999 the speaker examines the issues of modern social choice in the development of mankind. Civilizm is proposed as a new social system, and the characteristics of its constitutionalism, political system, and justice system are described. The author argues for the necessity of establishing a moral state and creating a union state with the participation of Russia by using the mechanisms of integration constitutionalism.